Value of Preoperative Imaging Results in Predicting Cochlear Nerve Function in Children Diagnosed With Cochlear Nerve Aplasia Based on Imaging Results - Chao, Xiuhua; Wang, Ruijie; Luo, Jianfen; Wang, Haibo; Fan, Zhaomin; Xu, Lei (Frontiers in Neuroscience, 2022)
This study aimed to assess the function of the cochlear nerve using electrically evoked compound action potential (ECAP) for children with cochlear implants who were diagnosed with cochlear nerve aplasia, and analyze the correlation between the pre-implantation imaging results and ECAP responses. Thirty-five children with cochlear nerve aplasia diagnosed by magnetic resonance imaging (MRI) were included. Pre-implantation MRI and high-resolution computed tomography (HRCT) images were reconstructed, and the width of bone cochlear nerve canal (BCNC), diameter of the vestibulocochlear nerve (VCN) and diameter of the facial nerve (FN) were measured. ECAP input/output (I/O) function were measured at three electrode locations along the electrode array for each participant. The relationship between ECAP responses (including ECAP threshold, ECAP maximum amplitude and slope of ECAP I/O function) and sizes of the BCNC and VCN were analyzed using the Pearson correlation test. Results shows that ECAP responses varied greatly among individual participants. Overall, ECAP thresholds gradually increased, and maximum amplitudes and ECAP I/O function slopes gradually decreased as the electrode location moved from basal to apical direction of the cochlea. No significant correlations were found between the ECAP responses and the BCNC width or VCN diameter. The diameter of the VCN to FN ratio showed a significant correlation with the slope of ECAP I/O function and maximum amplitude. BCNC width could not predict the function of cochlear nerve. Compared with the absolute size of VCN, the size of the VCN relative to the FN could potentially be used as an indicator for predicting the functional status of cochlear nerve in children with cochlear nerve aplasia.